Rare in the rare: Kikuchi-Fujimoto disease associated with connective tissue disorders. A report of our experience - Carmela Coccia; Gemma Lepri; Juela Levani; Silvia Bellando Randone; Serena Guiducci (Reumatismo)
Kikuchi-Fujimoto disease (KFD) is a rare and benign lymphadenopathy of unknown etiology. Usually, it is an isolated and self-limiting condition requiring no specific therapy; however, in some cases, it may be associated with an autoimmune disease. Here, we report three cases of KFD developing an associated autoimmune connective disorder: the first case presented with Sjögren's syndrome, and the other two had a diagnosis of systemic lupus erythematosus.